2015
DOI: 10.1094/phyto-11-14-0304-r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Stripe Rust Resistance in Wheat Lines with Resistance Gene Yr17 and Implications for Evaluating Resistance and Virulence

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici, has been the most important foliar wheat disease in south central United States since 2000 when a new strain of the pathogen emerged. The resistance gene Yr17 was used by many breeding programs to develop resistant cultivars. Although Yr17 was classified as a seedling (all-stage) resistance gene conferring a low infection type, seedlings with Yr17 frequently had intermediate to high infection types when inoculated with isolates that caused little or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…* Represents the clonal NW European lineage refering to many additional races prevalent in Europe up to 2010 .** Reference isolates from PstS1 provided by Gene Milus and extensively described in Milus et al (2015a,b) .*** Synonymous to “Triticale Aggressive” in Hovmøller et al (2016); v24/Avr24 could not be assessed due to avirulence on Avocet S .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…* Represents the clonal NW European lineage refering to many additional races prevalent in Europe up to 2010 .** Reference isolates from PstS1 provided by Gene Milus and extensively described in Milus et al (2015a,b) .*** Synonymous to “Triticale Aggressive” in Hovmøller et al (2016); v24/Avr24 could not be assessed due to avirulence on Avocet S .…”
Section: Resultsmentioning
confidence: 99%
“…** Reference isolates from PstS1 provided by Gene Milus and extensively described in Milus et al (2015a,b) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were grown in the field at INRA Le Rheu, Brittany, France, and inoculated with the yellow rust pathotype 237E141 AV17 as described in Dedryver et al () and Paillard et al (). A field resistance assessment showed that all plants carrying Yr17 were highly resistant at adult plant stages (Dedryver et al, , Paillard et al, and Milus, Lee, & Brown‐Guedira, ). Resistant plants and those with no obviously distinctive traits conferred by 6N v (height, pale‐green leaf, long peduncle) were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Milus et al () showed that yellow rust reactions on wheat seedlings with Yr17 were influenced by temperature, wheat genotype and pathogen isolate. Seedlings with Yr17 could have intermediate to high infection types when inoculated with isolates that caused little or no disease in adult plants of the same wheat lines.…”
Section: Discussionmentioning
confidence: 99%